The Role of Inclusion Benefits in Ethics Committee Assessment of Research Studies. Issue 3 (20th May 2019) - Rennie, Stuart; Day, Suzanne; Mathews, Allison; Gilbertson, Adam; Luseno, Winfred K.; Tucker, Joseph D.; Henderson, Gail E.
ABSTRACT: The relationship between risks and benefits is central to the ethics of research involving human participants. Traditionally, to be ethically justifiable, risks should be reasonable in relation to anticipated benefits (if any) to subjects and to the potential social benefits resulting from research. This calculus is being further complicated by findings from an increasing number of social science studies that reveal that prospective and actual research participants frequently describe various types of inclusion benefits (for example, personal benefits such as access to or improved health care, increased knowledge about their disease or condition, and greater solidarity with the local community) as important to them. What is the ethical significance of such inclusion benefits, particularly those nonmedical in nature, for research ethics committees' risk‐benefit assessment of research studies? We argue that, unless participants are clearly mistaken in their perceptions, ethics committees should take these types of inclusion benefits into account, and we suggest a few ways this might look in practice.